Знаряддя із вторинною обробкою пізньопалеолітичної стоянки біля с. Кам’янка - Сніжко, І.А. (Археологія і давня історія України, 2020)
Пізньопалеолітична стоянка біля с. Кам’янка на Харківщині належить до кола епіграветських пам’яток середньої течії р. Сіверський Донець. Стаття присвячена публікації колекції знарядь із вторинною обробкою. The tools with secondary treatment from collection of the Late Paleolithic site near the Kamyanka village of Izum district in Kharkiv region are published in the paper. The collection of 8356 flint artifacts comes from the excavated area of 225 m2. The group of the tools with secondary treatment is not large — it consists of 88 items (1.05 %), typical for sites located near flint raw material outputs, where primary treatment took place directly in the dwelling area. From 27 burins 16 are straight burins, 5 are angle burins, 5 are truncation burins, a flat-faceted burin, a many-faceted burin and a double burin. As a preform, the flakes, blades, massive flakes and residual cores were used. There are 12 end-scrapers and scrapers; end-scrapers on flakes and blades prevail. The tools with notches are represented by 9 exemplars. Working elements of the piercing tools (4 exemplars) are formed by several splits on the flakes; in one case the tool is combined with middle burin. 11 flakes and blades have retouched areas. Microblades with truncated edge are represented by 16 exemplars. Notched backed points (whole one and 2 fragments) have no analogs in collections of the sites of allied territories. A high trapeze on a wrong-shape blade, a massive blade with an angle unit pointed out by retouch, a chisel-like item, a disk-shaped tool with retouched area are represented in one exemplar for now. Generally the tools set is typical for Epigravettian sites, though the presence of notched backed points in it raises a range of questions which can be answered on during the further research.